Recreational spaces in the towns of Hungary - Aubert, Antal; Jónás-Berki, Mónika; Pálfi, Andrea (Journal for Geography, 2012)
The study is an introduction to recreational spaces in Hungary and an attempt for their typifying in relation with the Hungarian urbanisation processes and trends. In the first half of the essay the division of the urban spaces of Hungary is done, together with the introduction of the birth of the recreational spaces. The essay is continued with the typifying of the recreational spaces, differentiating intra- and extra-urban recreational spaces, giving examples from Hungary. The essay is finished by the introduction of a recreational space within Pécs and one around the city, with a view to their role in the recreation of the inhabitants and the leisure time possibilities.
Keywords: urbanisation; recreation; recreational spaces; Orfű; Pécs